Analisis Kesulitan Belajar Matematika dalam Menyelesaikan Soal Cerita Siswa Kelas V SDN Karawaci 1 - Anjani, Ayu; Unaenah, Een; Zamroni, Moh (TSAQOFAH, 2022)
This study aims to identify the difficulties faced by grade V students at SDN Karawaci 1 in solving story-shaped problems in mathematics subjects and identify factors that cause students to have difficulty learning mathematics. This research is a type of descriptive qualitative research with a case study approach. The subjects in this study were 5 grade V students of SDN Karawaci 1. Data collection techniques use observations, tests, interviews, and document studies. The results showed that the types of learning difficulties experienced by students in solving decimal fractional material story questions were 23 times students who had difficulty in understanding the questions, as many as 8 times students who had difficulty in using counting operations, as many as 11 times students who had difficulty solving questions, and as many as 21 times students who had difficulty in drawing conclusions. Factors that cause students to have learning difficulties are consisting of internal factors and external factors. Internal factors include students' attitudes in learning, student learning motivation, intellectual abilities and the health of the student's body. Meanwhile, external factors include the lack of variety of teaching methods used by teachers, the use of media that has not been maximized, school facilities and infrastructure, and a less supportive family environment.